Methylene tetrahydrofolate reductase gene mutation together with anticardiolipin antibody during pregnancy: a case report - Couto, Egle; Barini, Ricardo; Nomura, Marcelo Luís; Annichino-Bizzacchi, Joyce Maria; Silva, João Luiz Pinto e (São Paulo Medical Journal, 2002)
CONTEXT: High plasmatic homocysteine levels have been associated with arterial and venous thrombosis. The C677T methylene tetrahydrofolate reductase (MTHFR) gene mutation is one of the known causes for high homocysteine levels in plasma. Anticardiolipin antibody (ACA) is also associated with thrombosis and, along with other clinical complications such as recurrent abortion and stillbirth, is part of the antiphospholipid syndrome. DESIGN: Case report. CASE REPORT: A 19-year-old woman with two gestations and one parity (G2P1) had exhibited deep venous thrombosis in her previous puerperal period. Investigation of thrombophilic factors revealed ACA-IgM and heterozygous C677T mutation in the MTHFR gene. Lupus anticoagulant, protein C, protein S and antithrombin III deficiencies, and Leiden factor V and the G20210A mutation in the prothrombin gene, were not detected. The patient received 55,000 IU of subcutaneous heparin daily, from the 15th to the 36th week of pregnancy, when vaginal delivery took place. There were no clinical complications during the puerperal period and she was discharged three days after delivery, while still using oral anticoagulants.